An introduction to community development - Phillips, Rhonda; Pittman, Robert H. (London ; New York : Routledge, 2009)
"Beginning with the foundations of community development, this book offers a comprehensive and practical approach to planning for communities. Road-tested in the authors' own teaching, and also through the training they provide for practising planners, it enables students to begin making connections between academic study and practical know-how from both private and public sector contexts. An Introduction to Community Development shows how planners can utilise local economic interests and integrate finance and marketing considerations into their strategy. Most importantly, the book is strongly focused on outcomes, encouraging students to ask: what is best practice when it comes to planning for communities, and how do we accurately measure the results of planning practice? Each chapter provides a range of reading materials for the student, supplemented with text boxes, a chapter outline, keywords, and reference lists, making this the most user-friendly text now available."--BOOK JACKET.
Editors' Overview -- pt. 1. Foundations 1. Introduction to Community Development Robert H. Pittman and Rhonda Phillips 2. Seven Theories for Seven Community Developers Ronald Hustedde 3. Asset-Based Community Development Anna Haines 4. Social Capital and Community Building Paul Mattessich 5. Community Development Practice John W. Vincent II -- pt 2. Preparation and Planning 6. Community Visioning and Strategic Planning Derek Okubo 7. Establishing Community-Based Organizations Monieca West 8. Developing Community Leadership Skills for the New Economy David R. Kolzow 9. Community Development Assessments John W. Vincent II 10. Community Asset Mapping and Surveys Gary Paul Green 11. Assessing Your Local Economy: Industry Composition and Economic Impact Analysis William Hearn and Tom Tanner -- pt. 3. Programming Techniques and Strategies 12. Workforce Training For the Twenty-First Century Monieca West 13. Marketing the Community Robert H. Pittman 14. Retaining and Expanding Existing Businesses in the Community Robert H. Pittman and Richard T. Roberts 15. Entrepreneurship as a Community Development Strategy John Gruidl and Deborah Markley 16. Tourism-Based Development Deepak Chhabra and Rhonda Phillips 17. Housing and Community Planning Joseli Macedo 18. Neighborhood Planning for Community Development and Renewal Kenneth M. Reardon 19. Measuring Progress: Community Indicators, Best Practices, and Benchmarking Rhonda Phillips and Robert H. Pittman -- pt. 4. Issues Impacting Community Development 20. Community Development Finance Janet R. Hamer and Jessica LeVeen Farr 21. Securing Grants for Community Development Projects Beverly A. Browning 22. The Global Economy and Community Development David R. Kolzow and Robert H. Pittman 23. Sustainability in Community Development Stephen M. Wheeler -- 24. Conclusions and observations on the future of community developmet / Rhonda Phillips and Robert H. Pittman.
Includes bibliographical references and index.
Keywords: Community development; Economic development